'Breaking' the code. - Klein, Karen E. (Quill, 2001)
Deals with the problems posed by the Digital Millennium Copyright Act for computer scientists and journalists in the United States. Overview of the act; Details of a lawsuit filed by the Electronic Frontier Foundation in June 2001 in behalf of researchers who removed a digital watermark from a music file; Information on the arrest of Dmitry Sklyrov, a Russian computer programmer who worked on software that decrypts the Adobe eBook format.